Ultrasensitive real-time detection of Pb²⁺ ions using g-C₄N₄ nanosheets - Sharma, Nipun (2023)
The quick and easy monitoring of heavy metals in drinking water is utmost important due to their harmful effects on human health. In this work, a GaN-based high-electron-mobility transistor (HEMT) sensor has been fabricated using optical lithography and explored as a prospective sensor for the determination of trace Pb2+ ions present in the water. Graphitic carbon nitride (g-C3N4) was synthesized by a single-step combustion method. The g-C3N4 nanosheets were used to functionalize the gate area of the fabricated GaN HEMT sensor to investigate the presence of Pb2+ metal ions in water. The g-C3N4 functionalized sensor exhibited a sensitivity of around 0.46A /ppb with 0.32 ppb, as the limit of detection (LoD) is much below the international set standards. Moreover, the real-time measurements on lake water were performed using the developed GaN HEMT sensor to detect the presence of Pb2+ ions in real samples in a fast and ultrasensitive manner. We anticipate that the reported work will certainly serve as a proof-of-concept to develop heavy metal ion sensors.